1989
DOI: 10.1128/jcm.27.12.2827-2833.1989
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and geographical distributions of human rotavirus serotypes, 1983 to 1988

Abstract: and serotypes were determined for 907 of 1,084 clinical specimens of rotaviruses collected in various countries of Europe, North and South America, Africa, and Asia. Enhanced enzyme immunoassays based on monoclonal antibodies specific for rotavirus proteins VP6 and VP7 were used. Significant differences in the prevalent serotypes were detected from year to year in the United Kingdom and Brazil and also in different countries during the same year. Throughout the study, rotavirus serotype 1 was detected most oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 53 publications
8
48
0
1
Order By: Relevance
“…Eighteen studies reported that none of the rotavirus specimens possessed an unusual combination of serotype and electropherotype. However, several studies reported strains having an unusual combination of serotype and electropherotype (4,6,16,55,57,64,72,74). The frequency of the isolation of these rotaviruses varied from nil (0/605 in New England) (7) to 2.7% (9/335 in Bangladesh) (72).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen studies reported that none of the rotavirus specimens possessed an unusual combination of serotype and electropherotype. However, several studies reported strains having an unusual combination of serotype and electropherotype (4,6,16,55,57,64,72,74). The frequency of the isolation of these rotaviruses varied from nil (0/605 in New England) (7) to 2.7% (9/335 in Bangladesh) (72).…”
Section: Discussionmentioning
confidence: 99%
“…1) and G2. Serotype G2 strains possessing long RNA patterns have thus far been reported in six studies (1,6,31,43,65,72), and some were demonstrated by RNA-RNA hybridization to be reassortants between members of the Wa and DS-1 genogroups (35,72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the world, VP7 serotype G1 is detected most often, followed by G2, G3 and G4. 13 Each of the four serotypes has a worldwide distribution, with no single serotype being found exclusively in one location. 6 Serotype G1 is also predominant in Taiwan, as in many reports from all over the world.…”
Section: Rotavirus Vp7 Serotypes and Subgroupsmentioning
confidence: 99%
“…Large outbreaks of severe 0 1994 WILEY-LISS, INC. diarrhea in adults have been associated with Group B rotaviruses in several provinces of China [Hung et al, 19841, but not elsewhere. The Group C rotaviruses have been associated with either sporadic diarrheal illness or small outbreaks of diarrhea in infants and children in several different countries throughout the world [Beards et al, 1989;Bonsdorf and Svensson, 1988;Bridger et al, 1986;Brown et al, 1988;Caul et al, 1990;Chen et al, 1988;Dimitrov et al, 1983;Espejo et al, 1984;Matsumota et al, 1989;Nicholas et al, 1983;Penaranda et al, 1989;Rodger et al, 1982;Saif and Theil, 19851. Group C rotaviruses were isolated initially from diarrheic piglets in the United States [Saif et al, 19801, and limited surveys suggest this virus commonly infects pigs in North America, Europe, and Australia [Bohl et al, 1982;Nagesha et al, 1988;Saif, 1990;Saif and Theil, 19851.…”
Section: Introductionmentioning
confidence: 99%